Family Violence in Wives of Alcoholic and Non Alcoholic Related to Socio-Economic Status and Age: Exploring the Impact of Alcohol Abuse on Family Violence in Different Socio-Economic Contexts (Journal of Advances and Scholarly Researches in Allied Education, 2019)
An alcoholic drink is one of the most significant components of the worldwide market for abuse. Alcohol use is typically a big issue in developing countries like India as a consequence of diverse social-cultural norms around the country, varying alcohol policies and activities in different countries, a lack of societal knowledge of alcohol-related issues, misleading mainstream media advertising on alcohol usage, multiple levels of alcohol use of alcohol users and so forth. Alcoholics in multiple countries require strict alcohol laws to limit alcohol use, and users need to be told of the common adverse consequences of alcohol intake and their mind, body, and soul. This review article focuses on alcohol use as a consequence of its numerous adverse effects on the mind and body, as well as on alcohol policy in the region.